IMPLEMENTASI MEDIA LIVEWORKSHEET UNTUK MENINGKATKAN MOTIVASI BELAJAR BAHASA ARAB SISWA - Nabila Fahira Yahsan; Herpratiwi; Rangga Firdaus; Muhammad Nurwahidin (UNDIKMA, 2025)
Islamic-based character education is an important pillar in Indonesia, aiming to form students who have high morality and religious attitudes. The main goal of learning in schools is to create a pleasant atmosphere, which can attract the interest and enthusiasm of students, and motivate them to learn well. The challenges of Islamic Religious Education in the digital era are increasing, with technological innovations changing the learning paradigm. the development of livewoeksheet learning media is a relevant and innovative alternative. This media not only facilitates interactive learning, but also allows the integration of Islamic values through contextual exercises that can be accessed independently by students. This article aims to implement liveworksheet media to increase students' learning motivation. The research conducted was a development research with the ADDIE approach involving 29 students who had high, medium and low motivation, data analysis researchers used N-Gain analysis techniques. The results showed that there was a significant increase in student learning motivation after the application of Liveworksheets media. Before the use of the media, the average score of students' learning motivation was 4.48, which was classified in the good category. This increase was supported by observation and preliminary research which showed that the use of interactive media can provide a more interesting learning experience